2015
DOI: 10.1042/cs20140392
|View full text |Cite
|
Sign up to set email alerts
|

Role of indoleamine 2,3-dioxygenase in health and disease

Abstract: IDO1 (indoleamine 2,3-dioxygenase 1) is a member of a unique class of mammalian haem dioxygenases that catalyse the oxidative catabolism of the least-abundant essential amino acid, L-Trp (L-tryptophan), along the kynurenine pathway. Significant increases in knowledge have been recently gained with respect to understanding the fundamental biochemistry of IDO1 including its catalytic reaction mechanism, the scope of enzyme reactions it catalyses, the biochemical mechanisms controlling IDO1 expression and enzyme … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
216
0
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(225 citation statements)
references
References 604 publications
(1,238 reference statements)
6
216
0
3
Order By: Relevance
“…These include proinflammatory cytokines, and factors governing the synthesis of the haem prosthetic group that is essential for the formation of the active IDO1 holoenzyme (Yeung et al, 2015). These post-translational factors constitute novel targets for regulating stress-induced increased IDO1-KYN pathway activity.…”
Section: Ido1 Inhibition Blocks Kynurenine Pathway Activation and Excmentioning
confidence: 99%
“…These include proinflammatory cytokines, and factors governing the synthesis of the haem prosthetic group that is essential for the formation of the active IDO1 holoenzyme (Yeung et al, 2015). These post-translational factors constitute novel targets for regulating stress-induced increased IDO1-KYN pathway activity.…”
Section: Ido1 Inhibition Blocks Kynurenine Pathway Activation and Excmentioning
confidence: 99%
“…Its antimicrobial effect was thought to exist through a breakdown of TRP as TRP is essential for the growth of microorganisms. However, recent studies have demonstrated its novel role as a strong inhibitor of T cell proliferation [2]. Sepsis-induced elevation of 5-HT has recently been discovered in a mouse model where high levels of 5-HT facilitated endothelial hyperpermeability [3].…”
Section: Introductionmentioning
confidence: 99%
“…Particularly TRP and its metabolites are thought to be altered during infections as part of the immune reaction [2,3]. There are two metabolic pathways in the breakdown of TRP [4] (illustrated in Figure 1).…”
Section: Introductionmentioning
confidence: 99%
“…Many downstream products of KP have been identified as biologically active compounds (3)(4)(5), showing the capability to regulate inflammatory responses through several mechanisms [4]. An increasing body of evidence has thus thrust IDO1 under the spotlight as a key druggable target to control the balance between immune-tolerance and immune-inflammatory responses [5,6]. Noteworthy, signaling functions of IDO1 have also been discovered [7,8].…”
mentioning
confidence: 99%
“…The 95% of dietary L-Trp (1, Figure 1) is catabolized through the kynurenine pathway (KP), with IDO1 being a heme-containing enzyme that catalyzes the first and rate-limiting step of the pathway to produce N-formyl-kynurenine (2) [3]. Many downstream products of KP have been identified as biologically active compounds (3)(4)(5), showing the capability to regulate inflammatory responses through several mechanisms [4]. An increasing body of evidence has thus thrust IDO1 under the spotlight as a key druggable target to control the balance between immune-tolerance and immune-inflammatory responses [5,6].…”
mentioning
confidence: 99%